The inoculum ecology of Botrytis cinerea in Rooibos nurseries - Spies, Christoffel, F. J. (Christoffel Frederik Jakobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2005.